2016
DOI: 10.1590/s0100-204x2016000700012
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters for test-day milk yield in Khuzestan buffalo

Abstract: The objective of this work was to estimate covariance functions for additive genetic and permanent environmental effects, as well as to obtain genetic parameters for buffalo test-day milk yield using random regression models on Legendre polynomials (LPs). A total of 2,538 test-day milk yield (TDMY) records from 516 first lactation records of Khuzestan buffalo, calving from 1993 to 2009 and belonging to 150 herds located in the state of Khuzestan, Iran, were analyzed. The residual variances were modeled through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
1
2
2
Order By: Relevance
“…Sesana et al (2010) also found higher permanent environmental variances at early stages of lactation in milking buffalo while Madad et al (2016) reported highest permanent environmental variances in mid of lactation which was contradictory to the present findings. Katneni (2007), also obtained higher additive genetic and permanent environmental variance at the initial stage (0.991 and 1.716 kg 2 ) and end of lactation (1.997 and 2.019 kg 2 ) using LP function but obtained values were higher for additive genetic variance and lower for permanent environment variances in contrast to present estimates.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Sesana et al (2010) also found higher permanent environmental variances at early stages of lactation in milking buffalo while Madad et al (2016) reported highest permanent environmental variances in mid of lactation which was contradictory to the present findings. Katneni (2007), also obtained higher additive genetic and permanent environmental variance at the initial stage (0.991 and 1.716 kg 2 ) and end of lactation (1.997 and 2.019 kg 2 ) using LP function but obtained values were higher for additive genetic variance and lower for permanent environment variances in contrast to present estimates.…”
Section: Resultscontrasting
confidence: 99%
“…They estimated that genetic variances were higher (0.41) in the first month of lactation (DIM 30), declined to a value of (0.16) up to seven test days (DIM 210), and then increased to a maximum estimated value of (0.72) at DIM 270 for Iranian buffaloes. Similar findings using RRM were reported by Madad et al (2016) and Sesana et al (2010) and , who reported that Brazilian Murrah and Iranian Khuzestan buffaloes had higher additive genetic values for the first 2 weeks of lactation. Contrary to the present results, Tonhati et al (2008) reported lower estimates of the additive genetic variance at the beginning and end of lactation using a bivariate animal model.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations